What do principals do? : a study of a principal's job and how long it takes to do it - Hurst, Jonathan (Emerald Publishing Limited : Information Age Publishing, Inc., 2021)
"What Do Principals Do? provides a comprehensive and expansive look into a high school principal's job. Rather than a survey asking principals how much time they spend on various tasks, this work provides empirical evidence of exactly what a principal does every day of the year and how much time he spends doing it. Based on the results of a three-year longitudinal study conducted by a California High School Principal of the Year (Association of California School Administrator, 2012) , this book reveals precisely what a principal does, when he does it, and how much time he spends doing it. The study identifies 72 discrete tasks performed by principals and examines how much time (disaggregated by day, week, month, and year) they spend on each of those 72 tasks. The results of the data collection are the foundation of the book. The findings are supplemented with explanations and analyses that reveal the workings of K-12 education and give readers a glimpse of life in a comprehensive high school. This is a must read for everyone considering a life in public school administration. The author, Dr. Jon Hurst, the longest running principal in Elsinore High School's 129-year history, provides insightful commentary and relevant anecdotes from a rich and rewarding career served in a large comprehensive high school in Southern California. This book provides empirical evidence and an explanation for just what a principal does and how much time he spends doing it. In the process, it demonstrates the requisite skills for effective school governance, administrative multi-tasking, and productive principal behavior. Data collected covers three years and encompasses over 20,500 tasks and 7,500 hours of work. This is a useful augmentation to existing administrative credential course readings because it provides evidence for what the research and authors are saying and demonstrates those skills, procedures, and operations that are an everyday part of a school administrator's job. But the appeal for What Do Principal's Do? goes beyond those seeking knowledge about educational administration. Besides the facts and figures about how a principal spends his time, Dr. Hurst offers explanations for why and how the time is spent, and he provides insight into the educational scene. My book has appeal for students in teacher education programs, because it explains school communities and life in a school system, and that also makes it appealing to the lay person or parent who wants to understand how schools work"--